A szegénység elnőiesedése hat volt államszocialista országban - Fodor, Éva (Szociológiai Szemle, 2024)
Relying primarily on survey data from six East European countries, this paper seeks to answer two questions: 1) Are women over-represented among the poor population in Eastern Europe and if so, where? 2) What possible factors might explain the differences in the gender poverty gap across the countries under study? I find that three of the six countries exhibit significant gender differences in poverty: Russia, Romania and Bulgaria, and hypothesize that the speed of the economic transformations, as well as the resulting development of the welfare state will best explain the cross-country differences.